2017
DOI: 10.1080/16546628.2017.1399770
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of Lycium barbarum polysaccharides with different molecular weights: an in vitro and in vivo study

Abstract: The antitumor activity of Lycium barbarum polysaccharide (LBP) has been reported, but the structure-bioactivity relationship has still not been fully elucidated. In this study, four watersoluble LBP fractions with serial different molecular weights (MWs) were separated from LBP, designated LBP-2, LBP-3, LBP-4, and LBP-5. After a characteristic analysis, the relationship between MW and antitumor activity of LBP was investigated both in vitro using murine hepatoma H22 cells and in vivo using H22 tumor-bearing mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…The LBP fractions with different MW series, designated LBP2 (MW 350-400 kDa), LBP3 (MW 40-350 kDa), LBP4 (MW 8-40 kDa) and LBP5 (MW 3-8 kDa), were prepared as described in our previous study (Deng et al, 2017). The fractions were dissolved in cell culture medium and filtered through a 0.22 μm filter for in vitro experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LBP fractions with different MW series, designated LBP2 (MW 350-400 kDa), LBP3 (MW 40-350 kDa), LBP4 (MW 8-40 kDa) and LBP5 (MW 3-8 kDa), were prepared as described in our previous study (Deng et al, 2017). The fractions were dissolved in cell culture medium and filtered through a 0.22 μm filter for in vitro experiment.…”
Section: Methodsmentioning
confidence: 99%
“…LBP fractions of LBP-a4 with an MW of 10.2 kDa and LBP-p8 with an MW of 6.50 × 10 3 kDa had different effects on the proliferation of SMMC-7721 cells that LBP-a4 could inhibit the tumour cells growth while LBP-p8 showed opposite activity (Zhang, Tang, Wang, Zhang, & Zhang, 2013). In our previous study, we found that LBP fractions (named LBP2, LBP3, LBP4 and LBP5) with serial different MW had different inhibition activities in H22 cells growth in vitro and H22 tumour growth in vivo (Deng et al, 2017). In the present study, to further study the relationship of MW and immunomodulatory activity on the macrophage function of LBP, the effects of LBP fractions (named LBP2, LBP3, LBP4 and LBP5) with serial different MWs (range from 3 to 400 kDa) on RAW264.7 macrophages function were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…LBP was prepared from Lycium barbarum by our laboratory as described previously [ 23 ]. The total sugar and protein content was 70.13% and 19.30%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effect of LBP on systemic and local immune responses in vivo , especially on phenotypic and functional changes of T cells, is still largely unknown. In our previous study, we found that a fraction from LBP had the highest antitumor activity in H22 tumor-bearing mice [ 23 ]. In the present study, we further investigated the effect of LBP on immune responses both in system and tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Plants such as Lycium barbarum and L. chinense, also known as gou qi zi or Goji, wolfberry, Chinese wolfberry or matrimony wine, have been widely used in Asian countries for the treatment of a number of symptoms related to [12,19] diabetes, inflammation and as a tonic for well-being. The phytochemicals reported from Goji were claimed to exhibit antioxidant, antitumor, immunomodulatory, cardioprotective, antidiabetic and neuroprotective activities [19,20,21,22,23,24,25,26,27,28,29,30,31,32]. The dried root bark of L. barbarum, has been shown to produce long-term hypoglycemic effects and reduced body weight in diabetic mice [23].…”
Section: Introductionmentioning
confidence: 99%